2012
DOI: 10.14310/horm.2002.1377
|View full text |Cite
|
Sign up to set email alerts
|

The predictive role of 24h RAIU with respect to the outcome of low fixed dose radioiodine therapy in patients with diffuse toxic goiter

Abstract: radioactive iodine uptake (rAIU) is a test used to differentiate hyperthyroidism from thyroiditis and to calculate the radioiodine dose for treatment of Graves' disease. We aimed to evaluate the predictive role of 24h rAIU with respect to the outcome of radioiodine therapy in patients with diffuse toxic goiter (DTG). METHODs: case records of patients with DTG treated with radioactive iodine were reviewed retrospectively. Patients were divided into two groups based on 24h rAIU (normal range: 15% -35% at 24 h): … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…In their research, DeGroot et al also concluded that larger thyroid volumes need to be treated with higher dosages of 131 I per unit volume [44], and this has been confirmed by other studies too [45]. In our previous study, Damle et al [46], studied the effect of RAIU on 131 I therapy outcomes where the authors administered 5 mCi 131 I (mean activity) for the treatment of GD and reported the first-dose success rate of 81.7% in patients with 24-h RAIU < 50% and 68.6% in the group with 24-h RAIU > 50% (p < 0.001).…”
Section: Discussionsupporting
confidence: 71%
“…In their research, DeGroot et al also concluded that larger thyroid volumes need to be treated with higher dosages of 131 I per unit volume [44], and this has been confirmed by other studies too [45]. In our previous study, Damle et al [46], studied the effect of RAIU on 131 I therapy outcomes where the authors administered 5 mCi 131 I (mean activity) for the treatment of GD and reported the first-dose success rate of 81.7% in patients with 24-h RAIU < 50% and 68.6% in the group with 24-h RAIU > 50% (p < 0.001).…”
Section: Discussionsupporting
confidence: 71%
“…Studies have addressed the response to radioiodine therapy in relation to the radioiodine uptake and generally a high radioactive iodine uptake value is considered as a favorable factor for the success of radioiodine therapy [ 8 ]. However, studies by Damle et al [ 8 ] and Walter et al [ 9 ] have yielded conflicting results that showed an inverse correlation of pre-therapeutic iodine uptake level and therapeutic outcome. Standards regarding fixed doses were mainly based on studies done in iodine-replete countries, which may cause a lower radioactive iodine uptake value.…”
Section: Discussionmentioning
confidence: 99%
“…[1112] The good cure rates with low dose in our study population could be attributed due to relatively small diffused toxic goiters, probable relatively lesser iodine turnover, and persistent iodine-deficient state in a significant segment of Indian population despite universal iodization program implementation. Allahabadia et al ., reported that males are less likely to respond to a single dose of RAI[7] which is in line with study results in group B.…”
Section: Discussionmentioning
confidence: 94%